Effect of dietary threonine level on performance, egg quality and serum components in laying quails - Gül, ET; Olgun, O; Yıldız, A; Çolak, A (Journal of the Hellenic Veterinary Medical Society, 2024)
The current research was conducted to determine the effect of dietary threonine level on performance, egg quality, and serum components in laying quails. In the study, 120 female quails at 20 weeks of age were randomly allocated to six treatment groups with five replicates. Experimental diets were prepared to contain threonine at 0.750% (without addition, control), 0.825%, 0.900%, 0.975%, 1.050%, or 1.15% levels. The performance parameters did not affected by the threonine level of the diet, except for egg production (P>0.05). Egg production quadratically increased with the threonine level of the diet and it was maximum at 0.900% (P<0.01). Dietary threonine level quadratically affected eggshell thickness (P<0.05), but it did not affect other egg quality parameters in quails (P>0.05). Eggshell thickness improved up to 0.900% level, but decreased at higher threonine levels. The serum phosphorus concentration of laying quails was linearly affected by the threonine level and increased up to 0.900%, while it decreased at higher dietary threonine levels (P<0.01). According to the results obtained from the present study, it was determined that the threonine content of 0.900% in the laying quail diets was sufficient for optimum egg production, eggshell thickness, and phosphorus utilization.